2018
DOI: 10.5296/jas.v6i1.12262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Levels on Productivity and Fruit Quality of Tomato (Lycopersicon esculentum L.)

Abstract: Potassium has significant effect on quantity and quality of tomato yield because of its vital roles in photosynthesis, favoring high energy status and appropriate nutrient translocation and water uptake in plants. However, little is understood or it is being overlooked under Eritrean condition. Besides, poor soil fertility is among the major production constraints in Eritrea. The field experiment was therefore conducted to investigate the effect of potassium levels on productivity and fruit quality of tomato a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…chinense [69]. Thus, the level of potassium might indirectly affect capsaicin accumulation via its effects on fruit development [70]. CcABCC1 in C .…”
Section: Resultsmentioning
confidence: 99%
“…chinense [69]. Thus, the level of potassium might indirectly affect capsaicin accumulation via its effects on fruit development [70]. CcABCC1 in C .…”
Section: Resultsmentioning
confidence: 99%
“…Potassium fertilizer plays a major role in plant physiological process. It was reported [40] that fruit weight and fruits size increase with an increase in potassium fertilizer. Potassium has been noted to improve fruits quality by increasing the total sugar and total soluble solids in fruits [41].…”
Section: Discussionmentioning
confidence: 99%
“…2 A, B). Woldemariam et al (2018) assessed the effect of potassium levels (0,50,100,150,200,250,300,350 and 400 kg ha -1 of K 2 O) on productivity and fruit quality in tomatoes. The results of this study revealed that potassium had a significant effect on all yield and quality parameters.…”
Section: Analysis Of the Genotype-environment Interaction With The Ammi Modelmentioning
confidence: 99%
“…Additionally, K is involved in post-harvest quality of vegetables and fruits; it is associated with quality in products with a plant origin because of its important effects on post-harvest attributes, such as color, size, acidity, resistance to transportation, handling, storage, nutritional value, and industrial qualities (Javaria et al, 2012). Woldemariam et al (2018) assessed the effect of potassium levels (0,50,100,150,200,250,300,350 and 400 kg ha -1 of K 2 O) on productivity and fruit quality in tomatoes. The results of this study revealed that potassium had a significant effect on all yield and quality parameters.…”
Section: Analysis Of the Genotype-environment Interaction With The Ammi Modelmentioning
confidence: 99%